Characterizing the inhibitory action of zinc oxide nanoparticles on allergic-type mast cell activation. Issue 2 (August 2015) - Feltis, B.N.; Elbaz, A.; Wright, P.F.A.; Mackay, G.A.; Turney, T.W.; Lopata, A.L.
Highlights Mast cell degranulation can be inhibited by ZnO nanoparticles. This inhibition was nanoparticle size and dispersion dependent. ZnO nanoparticles had higher cytotoxicity to cancerous cells (RBL-2H3) compared to primary mast cells (BMMCs). TiO2 nanoparticles slightly increased mast cell degranulation. These nanoscale enhancements in ZnO bioactivity of may lead to the development of novel anti-allergic therapeutics.